2021
DOI: 10.3390/brainsci11101368
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Performance on Memory and Visuospatial Tasks in Functional Cognitive Disorder

Abstract: Functional Cognitive Disorder (FCD) is a common diagnosis at the memory clinic. FCD is characterised by significant self-reported cognitive symptoms in the absence of external evidence of cognitive dysfunction. A potential explanation for this is a deficit in metacognition, the process by which we internally judge our own abilities. Here we investigated differences in accuracy, confidence, and metacognition between people with FCD (N = 20), neurodegenerative mild cognitive impairment (nMCI; N = 14), and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…However, Pennington et al . 4 had previously reported that they ‘did not find metacognitive deficits in groups of well characterized patients with FCD’, a study finding not discussed by Bhome et al . This former report may thus potentially jeopardise proposed Bayesian and metacognitive models of FCD.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…However, Pennington et al . 4 had previously reported that they ‘did not find metacognitive deficits in groups of well characterized patients with FCD’, a study finding not discussed by Bhome et al . This former report may thus potentially jeopardise proposed Bayesian and metacognitive models of FCD.…”
mentioning
confidence: 85%
“…Both groups used forced choice (working) memory and (visual) perceptual tasks with trial-by-trial confidence ratings to assess metacognitive efficiency 3 or efficacy 4 with a hierarchical meta-d’/d’ model (ideal = 1). Although there were some methodological differences (e.g.…”
mentioning
confidence: 99%
See 3 more Smart Citations